2017
DOI: 10.1111/btp.12428
|View full text |Cite
|
Sign up to set email alerts
|

Species turnover in Amazonian frogs: low predictability and large differences among forests

Abstract: The factors explaining species turnover at different spatial scales have been intensively studied, but most work in Amazonia has mainly focused on plants. For animals, it is not as obvious which environmental variables most affect differences in species composition among sites. We sought to identify what causes anuran turnover in Amazonian terra firme forests, and how the effectiveness of these factors varies among regions and across spatial scales. We sampled frogs in 56 plots along ponds and streams distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Much of the PPBio effort directly concerns the distribution of species, but given the broad scope of the network, no taxonomic group dominates the research agenda. As biodiversity conservation is the ultimate goal of PPBio, many studies are on surveys and monitoring of populations and biological assemblages (e.g., Almeida-Gomes et al 2015, Moreira et al 2016, Bitar et al 2017, natural history (e.g., Magalhães et al 2013, Simões et al 2019, and description and analysis of the distribution of new species (e.g., Tourinho et al 2010Bellini et al 2013Aldrete & Neto 2014), filling critical knowledge gaps in all Brazilian biomes. A preliminary evaluation of output indicated that the Amazon still accounts for 55% of publications, followed by Atlantic Forest (17%), Caatinga (10%), Pantanal (6%), South Brazilian Grasslands (3%) and Cerrado (3%), but differences among biomes reflects to some extent biases in data reporting.…”
Section: Main Results Of Ppbiomentioning
confidence: 99%
“…Much of the PPBio effort directly concerns the distribution of species, but given the broad scope of the network, no taxonomic group dominates the research agenda. As biodiversity conservation is the ultimate goal of PPBio, many studies are on surveys and monitoring of populations and biological assemblages (e.g., Almeida-Gomes et al 2015, Moreira et al 2016, Bitar et al 2017, natural history (e.g., Magalhães et al 2013, Simões et al 2019, and description and analysis of the distribution of new species (e.g., Tourinho et al 2010Bellini et al 2013Aldrete & Neto 2014), filling critical knowledge gaps in all Brazilian biomes. A preliminary evaluation of output indicated that the Amazon still accounts for 55% of publications, followed by Atlantic Forest (17%), Caatinga (10%), Pantanal (6%), South Brazilian Grasslands (3%) and Cerrado (3%), but differences among biomes reflects to some extent biases in data reporting.…”
Section: Main Results Of Ppbiomentioning
confidence: 99%
“…A persistent problem is explaining how abiotic and biotic factors affect the distributions of species across spatial scales which are hierarchical in nature ( Fraterrigo, Wagner & Warren, 2004 ). Recent work has disentangled historical and environmental determinants for the spatial turnover of species assemblage compositions ( Ricklefs & Schluter, 1993 ; Holyoak, Leibold & Holt, 2005 ; Bitar et al, 2017 ). However, for single species, the main focus has been on predicting entire ranges by extrapolating from local data on habitat requirements (e.g., using species distribution models, see Elith & Leathwick, 2009 ; Zurell et al, 2016 ), for which an understanding of the potential hierarchy of controls on species’ niches is critically important ( Araujo & Luoto, 2007 ; Fraterrigo, Wagner & Warren, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…While sharp environmental boundaries clearly influence the abundance and occurrence of organisms, the effect of more gradual clines of biotic and abiotic features are less appreciated ( Quesada et al, 2012 ; Cintra et al, 2013 ; Emilio et al, 2013 ; Schietti et al, 2016 ). Under such a scenario, the abundance of organisms and patterns of local adaptation are shaped by continuous environmental changes across the landscape ( Endler, 1977 ; Leite & Rogers, 2013 ; Dias-Terceiro et al, 2015 ; Bitar et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in richness may also result from nestedness that occurs when species in a less rich locality are a subset of species of a richer community (Almeida-neto et al 2008). Understanding these patterns can provide insights into the processes that maintain biodiversity in communities subjected to frequent disturbances and help delineate conservation strategies (G omez-Rodr ıguez et al 2010, Machado et al 2012, Bitar et al 2017.…”
mentioning
confidence: 99%